2009
DOI: 10.1186/ar2617
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of lymphotoxin-beta receptor signaling reduces aspects of Sjögren's syndrome in salivary glands of non-obese diabetic mice

Abstract: Introduction The lymphotoxin-beta receptor (LTR) pathway is important in the development and maintenance of lymphoid structures. Blocking this pathway has proven beneficial in murine models of autoimmune diseases such as diabetes and rheumatoid arthritis. The aim of this study was to determine the effects of LTR pathway blockade on Sjögren syndrome (SS)-like salivary gland disease in non-obese diabetic (NOD) mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 42 publications
7
80
0
1
Order By: Relevance
“…3). Similar discordance has been noted in the NOD mouse when analyzing diabetes and salivary gland injury (46,65). Although this suggests that the mechanism of injury in these two organs may be different, it must also be considered that the mechanism of lung injury in IL14aTG mice is different from the mechanism of lung injury in IL14aTG.LTA 2/2 mice.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…3). Similar discordance has been noted in the NOD mouse when analyzing diabetes and salivary gland injury (46,65). Although this suggests that the mechanism of injury in these two organs may be different, it must also be considered that the mechanism of lung injury in IL14aTG mice is different from the mechanism of lung injury in IL14aTG.LTA 2/2 mice.…”
Section: Discussionmentioning
confidence: 51%
“…A recent study examining LTBR-Ig in NOD mice, an animal model for both diabetes and Sjögren's syndrome, confirmed that it blocked both the development of diabetes and sialitis. However, LTBR-Ig provided incomplete protection in maintaining normal salivary gland secretions (46). In contrast, a more recent study examining collagen-induced arthritis found that soluble LTBR-Ig had no influence on the disease, whereas Abs to LTA blocked disease induction and the aberrant production of cytokines associated with it (47).…”
Section: Discussionmentioning
confidence: 97%
“…baminercept and pateclizumab) may prove effective in blocking ELF activity. Although clinically untested for ELF‐associated inflammation, targeting LT β has shown promise in pre‐clinical experimental models of disease 126, 127, 128, 129. Similarly, CXCL13 blockade has shown some promise in pre‐clinical studies for the treatment of experimental inflammatory arthritis, diabetes and Sjögren syndrome 130, 131, 132.…”
Section: Concluding Remarks and Future Perspectives On The Therapeutimentioning
confidence: 99%
“…NOD H-2 h4 mice also develop a Sj€ ogren's Syndrome-like disease with infiltration of lymphocytes into the salivary gland of older female mice [40]. Treatment of NOD mice with LTbR-Fc for long periods of time reduces these structures [39]. Neutralization of CXCL13 IHC of frozen-spleen sections from mice treated with indicated molecules 9-11 days after immunization (similar splenic structure was noted for all groups 3-5 days after 2nd challenge).…”
Section: Cxcl13 Inhibition Alters Follicular Architecturementioning
confidence: 80%